Written production competences under a cognitive, procedural and contextual approach in agroindustrial engineering students (Gaceta Técnica, 2014)
The purpose of this study was to design a didactic proposal to improve literacy, aimed at Agroindustrial Engineering students at UCLA. It is focused on the reading cognitive approaches by Parodi (2003) and Marin (1999), the production procedural approach by Parodi (op. cit.) and Albarran (2005), and contributions about writing teaching under a contextual model by Hernandez and Quintero (2001). It is based on the qualitative approach with a classroom action-research design. The subjects consisted of 30 first semester students from Agroindustrial Engineering. A teaching proposal, containing development activities of 8 class sessions with their teaching resources and methodological theoretical justification was elaborated. The proposal is centered on three aspects: 1) Weaknesses and needs identified through an applied diagnosis, 2) Review and selection of updated information or academic significance about the literacy teaching to higher level, and 3) Classroom experience
Keywords: reading comprehension; written production; procedural approach; contextual approach